The Extent of Soil Drying and Rewetting Affects Nitrous Oxide Emissions, Denitrification, and Nitrogen Mineralization. Issue 1 (30th January 2014) - Guo, Xiaobin; Drury, Craig F.; Yang, Xueming; Daniel Reynolds, W.; Fan, Ruqin
Abstract : Soil drying and subsequent rewetting induces N mineralization and denitrification, but the effects of the "extent" or "degree" of drying and rewetting remains poorly understood. The impacts of different degrees of soil drying (drying to 45, 30, 20, or 10% water‐filled pore space, WFPS) and subsequent rewetting (rewetting to 75 or 90% WFPS) on N2 O emissions, denitrification, and net N mineralization were investigated. The highest N2 O emissions (201 µg N2 O‐N kg ‐1 ) occurred when the soils were dried to 10% WFPS followed by rewetting to 90% WFPS, whereas the lowest emissions (4.72 µg N2 O‐N kg ‐1 ) occurred when the soil was dried to 45% WFPS followed by rewetting to 75% WFPS. When soil was rewetted from 10 to 90% WFPS, cumulative N2 O emissions over 120 h were 7.4 times greater than when the soil was rewetted from 10 to 75% WFPS. The proportion of N2 O evolved [N2 O/(N2 O+N2 )] generally increased as the soil dried. Soil rewetting to 75% WFPS generally produced greater N2 O/(N2 O+N2 ) ratios than rewetting to 90% WFPS. Net N mineralization rates in soils rewetted to 75% WFPS significantly increased from 0.78 mg N kg ‐1 d ‐1 for the soils dried to 45% WFPS to 1.69 mg N kg ‐1 d ‐1 for the soils dried to 10% WFPS. More extensive soil drying and more extensive rewetting stimulated N2 O emissions and total denitrification losses, whereas net N mineralization rates were stimulated only by more extensive drying. Management practices which reduce extreme fluctuations in soil water content may consequently reduce N2 O and total denitrification losses.